A qualitative analysis of patients' experience with hospitalist service handovers. Issue 10 (11th May 2016) - Wray, Charlie M.; Farnan, Jeanne M.; Arora, Vineet M.; Meltzer, David O.
Abstract : BACKGROUND: Inpatient service handoffs occur when physicians who care for hospitalized patients end a period of clinical service and handover a panel of patients to an oncoming physician. Despite the large amount of research on handoffs, none has described the patient perspective when cared for by a hospitalist physician during a service handoff. OBJECTIVE: To describe hospitalized patients' experiences regarding inpatient service changes, and develop a conceptual framework to inform future efforts to improve service‐level handoffs. METHODS: Interview‐based qualitative analysis using in‐depth, semistructured interviews of hospitalized patients on a nonteaching hospitalist service. Patients were interviewed between October 2014 and December 2014 at an academic medical center whose inpatient stay spanned a weekly service change. We utilized an inductive approach with no a priori hypotheses and used a constant comparative method to generate emerging themes to develop a conceptual model that captured the patient experience during the transition. RESULTS: Of patients who agreed to participate (40/43), most (85%) were unaware that a transition had occurred between their hospitalists. Six major themes emerged related to patients' experiences with hospitalist service handoffs: (1) importance of physician‐patient communication, (2) desire for transparency in transitions, (3) an indifference toward transitions, (4) importance of hospitalist‐specialist communication, (5) formation of new opportunities from a transition, and (6) effects of bedside manner. CONCLUSIONS: Hospitalized patients desire improved communication and a more formalized transition process between hospitalists during service handoffs. Hospitalists should recognize that this transition may represent an opportunity to improve the hospitalized patient's experience and satisfaction. Journal of Hospital Medicine 2016;11:675–681. © 2016 Society of Hospital Medicine